Cultivo del Palto: Persea americana Mill - Londra, Beatriz Carolina; Ala, Joaquín; Gorelik Zonis, Yanina Gisela (Estación Experimental Agropecuaria Concepción del Uruguay, INTA, 2025)
EEA Concepción del Uruguay